Rapid and sensitive quantitative immunoassay for the large simian virus 40 T antigen. - Kilton, L J (1981)
A quantitative, enzyme-linked immunoadsorbent assay has been developed for the simian virus 40 large T antigen. When hamster anti-simian virus 40 tumor serum was used, this method permitted specific identification of large T antigen and its analog, the D2 hybrid protein, a molecule with the same C-terminal approximately 600 amino acids as large T antigen. The sensitivity limit of this test was 0.63 ng of protein. The slopes of the regression lines of the enzyme-linked immunosorbent assay titrations performed with highly purified D2 or simian virus 40 large T antigen and with crude extracts of simian virus 40-infected monkey and transformed human cells were identical. Thus, the curve generated with a purified protein, such as D2, can serve as a quantitative standard for the measurement of large T antigen in a wide variety of extracts. Furthermore, solutions containing high salt concentrations and buffers containing up to 0.1% Nonidet P-40 did not interfere with the assay, making it applicable to the measurement of large T antigen in a variety of chromatographic fractions. The enzyme-linked immunosorbent assay was three times more sensitive, was significantly faster to perform, and was quantitatively valid over a much broader large-T-antigen concentration range than the complement fixation test. As such, it should be useful in future studies of the structure and function of this protein.